2022
DOI: 10.3390/pharmaceutics14122642
|View full text |Cite
|
Sign up to set email alerts
|

Development of Ag-ZnO/AgO Nanocomposites Effectives for Leishmania braziliensis Treatment

Abstract: Tegumentary leishmaniasis (TL) is caused by parasites of the genus Leishmania. Leishmania braziliensis (L.b) is one of the most clinically relevant pathogens that affects the skin and mucosa, causing single or multiple disfiguring and life-threatening injuries. Even so, the few treatment options for patients have significant toxicity, high dropout rates, high cost, and the emergence of resistant strains, which implies the need for studies to promote new and better treatments to combat the disease. Zinc oxide n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…The nanocomposites used here were named ZnO:5Ag (49%), ZnO:9Ag (65%) and ZnO:11Ag (68%); this nomenclature corresponds to the percentage of AgO nanocrystals found in their structure. Structural and morphological properties of ZnO nanocrystals and Ag-ZnO/AgO nanocomposites were previously characterized by [ 9 , 10 ] and are shown in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The nanocomposites used here were named ZnO:5Ag (49%), ZnO:9Ag (65%) and ZnO:11Ag (68%); this nomenclature corresponds to the percentage of AgO nanocrystals found in their structure. Structural and morphological properties of ZnO nanocrystals and Ag-ZnO/AgO nanocomposites were previously characterized by [ 9 , 10 ] and are shown in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…It has already been reported that this combination (Ag-ZnO/AgO NPs) was able to enhance the microbicidal potential against Prevotella intermedia , Salmonella sp. [ 9 ] and Leishmania braziliensis [ 10 ]. Further, Ag-ZnO/AgO NPs have been shown to have antioxidant, anti-inflammatory and skin-lesion healing potential when administered topically in mice [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…58,60 Furthermore, they have shown efficacy in controlling parasites such as tegumentary Leishmaniasis. 61,62 3.4. Au-Doped ZnO Nanocrystals Exhibit Higher Biocompatibility in Fruit Flies.…”
Section: Antimicrobial Activity Assaysmentioning
confidence: 99%
“…ZnO NPs, obtained through different chemical and green synthesis routes, have been widely applied in antimicrobial perspectives, showing promising performance against both Gram-positive and Gram-negative bacteria, although limitations regarding their spectrum of action have been observed. In this context, the combination with other metallic nanoparticles, such as ZnO/AgNPs and Co–ZnO NPs, has been a strategy used to enhance the antimicrobial effect of the nanoproduct. , Although this study did not directly compare nanoproducts obtained from the incorporation of other metallic nanoparticles, recent studies present results similar to ours, reporting an improvement in antimicrobial activity with the incorporation of the nanoparticles. Furthermore, there is evidence that the incorporation of Au NPs exhibits better antimicrobial performance compared to the Ag/ZnO NP combination. , Doping of ZnO with metallic nanoparticles such as Ag has also been shown to be effective in controlling resistant bacteria. , Furthermore, they have shown efficacy in controlling parasites such as tegumentary Leishmaniasis. , …”
Section: Antimicrobial Activity Assaysmentioning
confidence: 99%
See 1 more Smart Citation